The optimization of trunk position for the 2016 rio paralypmic wheelchair racing finals - Lewis, A.; Phillips, E.; Moore, V.; Bartram, J.; Grimshaw, P.; Portus, M.; Robertson, W. S. P. (ISBS Proceedings Archive (Michigan), 2017)
This research investigated the relationship between athlete aerodynamics (based on peak frontal area during recovery phase) and finishing position for athletes in the 100m- 5000m wheelchair Athletics events. A retrospective analysis was performed on T54 classified male and female finalists (n=86) at the 2016 Rio Paralympic Games. Medalling female athletes more consistently favoured an aerodynamic position than was observed for males, who may be more inclined to overcome additional resistive forces through powerful techniques due to enhanced strength capacities. Whilst aerodynamics does not appear the sole performance requirement for male athletes, time savings of up to 116s over a 5000m race can be obtained, if athletes improve their aerodynamics, without compromising force generating capacity, demonstrating its importance to athletes.